Strategi pengembangan agrowisata kopi rakyat di Jawa Timur: Developing strategy of community based coffee agrotourism in East Java - Hidayat, Fajar Rasyidi; Hakim, Luchman; Parmawati, Rita (Fakultas Pertanian Universitas Yudharta Pasuruan, 2023)
Introduction: The development of smallholder coffee agro-tourism in East Java is the development of local community-based tourism destinations. The development was ideal if there was an increase in community participation, an increase in the local economy, and a contribution to conservation. However, in the initial study, there were several problems that caused smallholder coffee agro-tourism in East Java to lack competitiveness. This study aims to analyze the key factors that can be used as a reference in the right strategy in developing smallholder coffee agro-tourism in East Java. Methods: This study uses mixed methods using qualitative and quantitative data. Data analysis using Prospective Analysis with the contribution of the experts Results: The results showed that there were 29 factors that influenced the development of smallholder coffee agro-tourism in East Java. After conducting a prospective analysis, there are 17 key factors that become a reference in determining the development strategy. These factors include (1) product management with environmental and health principles, (2) land ownership status, (3) products sold by farmers, (4) community relations, (5) coffee plant care, (6) product prices, (7) transparency of product prices, (8) monitoring and evaluation, (9) opportunities to get jobs, (10) variety of tour packages, (11) conditions of socio-cultural objects, (12) local cultural conditions of coffee plantation communities, (13 ) fair wages for coffee farmers and the community, (14) agro-tourism management reports, (15) availability of souvenir shops, (16) coffee distribution system, and (17) coffee agro-tourism legality. Conclusion: The implementation of this strategy can be carried out by synergies and collaborations between tourism stakeholders consisting of village governments, the tourism industry, universities, non-governmental organizations, and the media.